2022
DOI: 10.1111/acps.13425
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and ECT, ECT and suicidal ideation: A register study

Abstract: Objective Although electroconvulsive therapy (ECT) is anti‐suicidal, it is not known whether the presence of suicidal ideation (SI) at baseline predicts response and remission after ECT. The aim of the study was to analyze the impact of baseline SI on response and remission following ECT treatment in a large sample of patients with depression and to assess SI before and after ECT. Methods This population‐based register study used data from the Swedish National Quality Register for ECT and the Swedish Patient R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Sienaert et al. (2022) found the response rate of ECT for MDD adults with SI was 53.7%, but in MDD adults without SI, the response rate was 68.5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sienaert et al. (2022) found the response rate of ECT for MDD adults with SI was 53.7%, but in MDD adults without SI, the response rate was 68.5%.…”
Section: Discussionmentioning
confidence: 99%
“…For MDD adolescents with suicidal symptoms, previous studies showed worse outcome compared with MDD without suicidal symptoms (Grover et al, 2013;Puffer et al, 2016;Zhang et al, 2012), but we don't know the response rate of different suicidal symptoms, such as SI and SA, and if they showed different clinical outcome based on ECT. Sienaert et al (2022) found the response rate of ECT for MDD adults with SI was 53.7%, but in MDD adults without SI, the response rate was 68.5%, and they did not discuss the response rate of SA. To our best knowledge, there are no randomized controlled trials to determine the efficacy of ECT in adolescents with depression and suicidal symptoms, so we try to find out the efficacy and safety in a retrospective series of adolescents hospitalized with different suicidal symptoms.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Treatment remission rates may be as high as 60%-70%. 25 26 Further, ECT rapidly reduces suicidal ideation, [27][28][29] death by suicide 30 and significantly improves quality of life. 31 The efficacy, safety and acceptability of modern ECT practices are the result of several major advances in treatment delivery since the technique's development in the 1930s.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The anti-suicidal effect of ECT across mental disorders is well-established [6][7][8][9][10][11][12][13][14][15][16]. However, because the "baseline" risk of suicide among patients receiving ECT is highly elevated, suicide remains a relatively common cause of death for those having received ECT [17][18][19].…”
Section: Introductionmentioning
confidence: 99%